Digital Marketing Strategy to Increase Sales Conversion on E-commerce Platforms - Purnomo, Yudiyanto Joko (ADMAN: Journal of Contemporary Administration and Management, 2023)
In this digital era, technological developments have significantly changed the business paradigm, especially in the e-commerce industry. E-commerce platforms have become one of the main media for many companies to sell their products and services online. However, the increasing number of competitors on e-commerce platforms requires companies to have an effective marketing strategy to increase sales conversion and gain a competitive advantage. The purpose of this research is to analyse and identify effective digital marketing strategies in increasing sales conversion on e-commerce platforms. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that in an effort to increase sales conversions on e-commerce platforms, digital marketing strategies play a crucial role. By combining various techniques and tactics, you can achieve successful results in increasing traffic, engagement, and ultimately, sales conversions on your e-commerce platform. Here are the core digital marketing strategies including SEO, content marketing, social media, paid advertising, user experience optimisation, customer reviews and testimonials, content personalisation, video usage, incentives, and car optimisation.